Soundecology indicators applied to urban parks: a preliminary study - Benocci, Roberto; Brambilla, Giovanni; Bisceglie, Alessandro; Zambon, Giovanni (Asia-Pacific Journal of Science and Technology, 2020)
In soundscape ecology, different acoustic indices have been developed to describe the acoustic environment, mainly in natural areas. Avian species are among the sources of natural sounds that positively influence the human perception of a natural environment. However, the acoustic environment is rather complex due to the contemporary presence of different sources, leading to the difficult task of discriminating these sources in audio data. This task is even more essential in medium-large urban parks, as they are often exposed to road traffic noise produced by surrounding roads and to anthropogenic sounds due to people using the park for different purposes. Such non-natural sounds can deteriorate the perceived soundscape quality of the park and, therefore, reduce its potential restorative function. The aim of this preliminary study is to evaluate the potential of sound ecology indicators for discriminating the different types of sounds present in medium-large urban parks. For this purpose, two environmental settings were considered: a large urban park surrounded by busy roads and a shrub-dominated area, the latter of which was used as a reference site for natural areas. The two sonic environments were characterized by the presence of different anthropogenic noises, especially in the urban park, and sounds from avian species. Sound ecology indicators, or their combinations, could help identify the urban park areas with higher biophonic activities and, therefore, the areas that offer greater relief and restorative value. Such information can be helpful for improving the use of parks by directing users towards areas with features more conducive to their enjoyment and consistent with their expectations.